Multilayer microneedle array patches by combining inkjet printing and micromolding - A technical evaluation (Transactions on Additive Manufacturing Meets Medicine, 2023)
Microneedle array patches offer the possibility to deliver active pharmaceutical ingredients bypassing the gastrointestinal tract. Dissolvable microneedles pierce the stratum corneum, dissolve under the skin and release the drug to the body. Inkjet printing is known to be a possible manufacturing method for microneedle array patches and a suitable tool for preparing personalized medicine. Multilayer microneedle array patches consist of at least two layers clearly separated from each other. A suitable ink candidate for the production of the first layer of microneedles has been found. The printing process was optimized, and the jetted droplets were analyzed in terms of their velocity and volume. Lisinopril has been used as a model drug with a peptidomimetic structure.  Different heights of the drug-containing layer of the microneedles were successfully produced resulting in the possibility to vary the dosage of the microneedle array patches between 11.5 – 34 µg. The production was successful resulting in sharp and intact needle tips and the microneedles did not shrink. The height of the needle tips was precisely adjusted. The produced microneedle array patches showed good mechanical properties and did not break during the simulation of the application procedure. Testing the insertion into an artificial skin membrane model resulted in at least 381 µm insertion depths. Therefore, these multilayer microneedle array patches were promising candidates to enable efficient drug delivery. Inkjet printing could be used as a precise manufacturing method for personalized medicine with varying dosages of microneedle array patches for the patients’ needs. Multilayer microneedle array patches are promising candidates for adjusting the dissolution profile of dissolvable microneedles by preparing several layers from various polymers and combining these polymers in one single microneedle array patch. Different drug substances may be combined in a single patch. AcknowledgmentsThe authors would like to thank LTS Lohmann Therapie-Systeme for kindly providing the silicon molds for the production of microneedle array patches. The authors would like to thank Dr. Tobias Auel and Lee Roy Oldfield (Heinrich Heine University Duesseldorf) for preparing sample holders by fused deposition modeling (3D printing) to dry the microneedle array patches.Author’s statementThe authors state no conflict of interest. Informed consent has been obtained from all individuals included in this study.
Keywords: Transdermal Drug Delivery; TDDS; Microneedles; Microneedle Array Patches; Inkjet Printing; Drug Printing